PROSEDUR PEMERIKSAAN RADIOGRAFI VERTEBRA THORAKOLUMBAL PADA KLINIS SKOLIOSIS - Muhammad Ridwan Eko Budidarmawan; Fatimah Fatimah; Sugiyanto Sugiyanto (JRI (Jurnal Radiografer Indonesia), 2022)
The procedure of radiographic examination of thoracolumbar vertebrae of scoliosis according to Lampignano and Kendrick (2018), journal by Gray (1983) and journal by Levy (1996) in erect patient position further recommends the PA projections because the dose to organs that are sensitive to radiation such as breast, thyroid and gonad and the risk of getting cancer in these organs is significantly reduced compared to AP projections. While the procedure for radiographic examination of thoracolumbar vertebrae of scoliosis in the Radiology Installation RSUD Bendan Pekalongan uses AP and AP right and left bending projections in erect patient position. This study aims to determine the radiographic examination procedures of thoracolumbar vertebrae in scoliosis and the reasons for using AP and AP right and left bending projections in erect patient position. This type of research is a qualitative research with a case study approach. Data was collected in March-April 2020 in the Radiology Installation RSUD Bendan Pekalongan by observation, interview and documentation. Research subjects are patients, radiographers, radiology specialists, and sending doctors. The data obtained were processed and analyzed using open coding and then presented in the form of images, plot and quotations so that conclusions can be drawn. The results showed that the thoracolumbar vertebra radiographic examination procedure in scoliosis clinical in Radiology Installation RSUD Bendan Pekalongan used AP and right and left bending AP projections in erect position because to place the object as close as possible to IR with the hope to minimize the magnification of the object on the radiograph and has been informative to assess the cobb angle in scoliosis curvature. The suggestion from the author is that Radiology Installation should coordinate with related parties such as radiology specialists, radiographers and sending doctors in order to determine what projections are needed in the case of scoliosis because there are many projections on the scoliosis radiography examination.